Assessment of the effects of scanning and reconstruction parameters on bone densitometry results for single energy quantitative CT (qCT) scans in a phantom study - Hofmann, Philipp; Lenhart, Björn; Sedlmair, Martin; Schmidt, Bernhardt; Flohr, Thomas; Mahnken, Andreas (European Congress of Radiology, 2016)
Keywords: Musculoskeletal spine; Bones; Computer applications; CT-Quantitative; CT; Absorptiometry / Bone densitometry; Computer Applications-Detection; diagnosis; Physics; Osteoporosis; Demineralisation-Bone

Evaluation of a Robust Correlation based True-Speed-over-Ground Measurement System employing a FMCW Radar - Reißland, Torsten; Lenhart, Björn; Lichtblau, Johann; Sporer, Michael; Weigel, Robert; Kölpin, Alexander (International Journal of Microwave and Wireless Technologies, 2019)
This paper presents a novel approach for the determination of True-Speed-Over-Ground for trains. Speed determination is accomplished by correlating the received signals of two side-looking radar sensors. The theoretically achievable precision is derived. Test measurements are done in two different scenarios to give a prove of concept. Thereafter a series of field measurements is performed to rate the practical suitability of the approach. The results of the measurements are thoroughly evaluated. The test and field measurements are carried out using a 24 GHz frequency modulated continuous wave (FMCW) radar.

Evaluation of ISAR-based autofocus methods for estimation of true-speed-over-ground using a 24 GHz FMCW-Radar - Reißland, Torsten; Lenhart, Björn; Lichtblau, Johann; Sporer, Michael; Kölpin, Alexander; Weigel, Robert (Asia-Pacific Microwave Conference, 2019)
This paper presents a novel approach for the determination of True-Speed-Over-Ground for trains. The approach utilizes the inverse synthetic aperture radar (ISAR) technique. Several focus metrics are evaluated and tested. The tests were carried out in an laboratory environment. The results are compared to an alternative correlation-based approac
Keywords: focusing; measurement systems; synthetic aperture radar; velocity measurement

Robust Correlation based True-Speed-over-Ground Measurement System employing a FMCW Radar - Reißland, Torsten; Lenhart, Björn; Lichtblau, Johann; Sporer, Michael; Weigel, Robert; Kölpin, Alexander (2018 15th European Radar Conference (EuRAD), 2018)
This paper presents a novel approach for the determination of True-Speed-Over-Ground for trains. Speed determination is accomplished by correlating the received signals of two side-looking radar sensors. The theoretically achievable precision is derived. Test measurements are done to give a prove of concept. The measurements are done in two different scenarios. The test measurements are carried out using a bi-static 24 GHz frequency modulated continuous wave (FMCW) rada
Keywords: radar; fmcw; correlation; sar; velocity; train